Research on Power Price Pricing Method of Distribution Network Nodes Considering Energy Saving and Emission Reduction of Distributed Power Sources and Market Game Behavior - Zhang, Jia; Dong, Jinxi; Xu, Zhenbo; Wang, Jiawei; Liu, Huiqing; Zhang, Yanjuan; Ji, Shuanmei; Li, Xiaoying (2018 2nd IEEE Conference on Energy Internet and Energy System Integration (EI2), 2018)
Under the market environment in which the distribution business is released in an orderly manner, the market behavior of the distributed power generation (DG) operating entity will further increase the uncontrollability of its output. The main body of the distribution network needs to intervene and control the output of the DG to a certain extent by using electricity prices and other means to reduce the uncertainty caused by the distributed power access. To this end, this paper proposes a distribution network node price pricing method based on the market cooperation game concept, considering the distribution of gas emission reduction tasks in distribution networks, according to the priority of gas emission reduction and distribution network operation subject income, Applying its best coping strategy to the calculation of node price to compensate the price of distributed power units participating in energy conservation and emission reduction, improve the control and management level of distribution network operators for a single distributed power unit and multiple distributed power unit combinations in the region.